2010
DOI: 10.1186/1471-2164-11-38
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput SNP discovery through deep resequencing of a reduced representation library to anchor and orient scaffolds in the soybean whole genome sequence

Abstract: BackgroundThe Soybean Consensus Map 4.0 facilitated the anchoring of 95.6% of the soybean whole genome sequence developed by the Joint Genome Institute, Department of Energy, but its marker density was only sufficient to properly orient 66% of the sequence scaffolds. The discovery and genetic mapping of more single nucleotide polymorphism (SNP) markers were needed to anchor and orient the remaining genome sequence. To that end, next generation sequencing and high-throughput genotyping were combined to obtain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
194
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 252 publications
(202 citation statements)
references
References 19 publications
6
194
1
1
Order By: Relevance
“…It is possible that the parents shared large regions of their genomes that were identical because of descent from common ancestors (Kassem et al 2006;Lightfoot et al 2008) but this would be more extreme than reported previously. There are soybean transcript maps and consensus map reported by Choi et al (2007) (2,389 cM: total 2,982 markers including 1,361 SNP markers,) and Hyten et al (2010) (2296.4 cM: total 5,500 markers including 3,792 SNP markers) respectively. However, these maps are not comparable to the map reported here as they were composed from multiple marker types and several populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the parents shared large regions of their genomes that were identical because of descent from common ancestors (Kassem et al 2006;Lightfoot et al 2008) but this would be more extreme than reported previously. There are soybean transcript maps and consensus map reported by Choi et al (2007) (2,389 cM: total 2,982 markers including 1,361 SNP markers,) and Hyten et al (2010) (2296.4 cM: total 5,500 markers including 3,792 SNP markers) respectively. However, these maps are not comparable to the map reported here as they were composed from multiple marker types and several populations.…”
Section: Discussionmentioning
confidence: 99%
“…To date, random amplified polymorphic DNA (RAPD), restriction fragment length polymorphisms (RFLP), amplified fragment length polymorphism (AFLP), simple sequence repeat (SSR), and single nucleotide polymorphism (SNP) markers have been used to construct genetic linkage maps and a consensus map in soybean using many different mapping populations (Shoemaker et al, 1995;Lark et al, 1995;Keim et al, 1997;Song et al, 2004;Cregan et al, 1999;Song et al, 2004;Kassem et al, 2006Kassem et al, , 2012Choi et al, 2007;Hyten et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In human, about 90% of variation is attributed to SNPs, equating to approximately 1 SNP in every 100-300 bases. Based on partial genomic sequence information from barley, soybean, sugarbeet, maize, cassava, potato and other crops, typical SNP frequencies are also in the range of one SNP every 100-300 bp (Edwards et al, 2007;Hyten et al, 2010). Rice serves a crop model and, therefore, discovery and utilization of SNP markers in rice can be enhanced and perfected for other crop plants.…”
Section: Single Nucleotide Polymorphism (Snp)mentioning
confidence: 99%
“…However, random approaches based on restriction digestion and transcriptome sequencing are more adequate in most genome-wide projects (Deschamps & Campbell, 2010). The use of methylation-sensitive enzymes or endonucleases that preferentially cut in low copy DNA have been particularly successful when used in strategies to identify large sets of SNPs in maize and soybean varieties (Gore et al, 2009b;Deschamps et al, 2009;Hyten et al, 2010). Illumina-based SNP discovery strategies using reduced representation libraries (RRLs) have been described by Deschamps and colleagues in soybean.…”
Section: Genomic Variant Discovery For Marker Developmentmentioning
confidence: 99%